Securing a life for the dead among the Yukpa. The exhumation ritual as a temporary synchronisation of worlds - Ernst Halbmayer (Journal de la Société des Américanistes)
This paper presents a description and analysis of the Yukpa exhumation ritual. The ritual is explained from an alterity-based socio-cosmological point of view based on the assumption that the internal structure of the death ritual only reveals itself if the existence of the co-present worlds of the living and the dead are used as a point of departure together with the concomitant transformative and perspectivist quality of the ritual. The Yukpa secondary burial aims to effect specific changes in the perspectives and relations of the participants and produces a synchronisation between these worlds and thereby facilitates the necessary contact and transition between them. This passage is neither marked by a radical divide between the dead and the living nor by an unbroken continuity, but by a gradual transformation that culminates in a « de-burial » (desentierro) followed by a secondary burial.